Circular RNA circ0104103 inhibits colorectal cancer progression through interactions with HuR and miR‐373‐5p. Issue 4 (11th January 2023) - Tan, Pei; Sun, Huiling; Xu, Mu; Liu, Xiangxiang; Qin, Jian; Nie, Junjie; Qin, Xiaodan; Wang, Shukui; Pan, Yuqin
Abstract: Emerging evidence has suggested that circular RNAs (circRNAs) have vital functions during the initiation and progression of various diseases. However, circRNA potential mechanisms in colorectal cancer (CRC) are largely unknown. Here, we sought to investigate the role and underlying regulatory mechanism of circ0104103 in CRC. circ0104103 was validated by quantitative RT‐PCR (qRT‐PCR) and Sanger sequencing. Gain‐ and loss‐of‐function assays in cell lines and mouse xenograft models were utilized to investigate the effects of circ0104103 in CRC. RNA pull‐down assays, RNA immunoprecipitation assays, bioinformatics analyses, RNA FISH, and luciferase reporter assays were used to elucidate the potential mechanism of circ0104103 in CRC. We identified circ0104103, which is strongly downregulated in CRC tissues and cell lines. Functional studies revealed that circ0104103 inhibited CRC cell growth, migration, and invasion both in vitro and in vivo. Mechanistically, circ0104103 binds to HuR, a functional RNA‐binding protein commonly expressed in CRC. HuR binds to the 3′UTR of LACTB mRNA to facilitate stabilization and increase its expression. Moreover, circ0104103 was verified as a competing endogenous RNA (ceRNA) via negative regulation of miR‐373‐5p to increase LACTB expression, resulting in inhibiting the occurrence and progression of CRC. Taken together, our study revealed that circ0104103 acts as a tumor suppressor and may be a novel biomarker and therapeutic target in CRC. Abstract : Circ_0104103 interacts with HuR to promote the stability of LACTB mRNA, thereby enhancing its expression. Moreover, Circ_0104103 functions as a sponge of miR‐373‐5p to regulate LACTB expression. Due to its dual targeting effects on LACTB, targeting Circ_0104103 in combination with other therapies may achieve better therapeutic efficiency.